PERANAN PASAR WISATA TERHADAP PENDAPATAN DAERAH DI OBJEK WISATA TUK-TUK - Vina Arnita (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This study aims to describe the profile and existence in Tuk-Tuk including explaining management strategies and their contribution to regional development. The research approach used is a quantitative method with descriptive analysis techniques. This is evident from the condition of market infrastructure that has been adequately supported by the participation of traders, consumers, and government who really pay attention to the implementation of programs, innovations, and market promotions. So Samosir Market has a big contribution not only spatially and socially culture, but also to support the regional economy and tourism. This study examines whether the variable Technology Development, on regional income. Then the data obtained were analyzed using multiple regression analysis. The results of the study stated that the variable of the development of science and technology had a significant effect on the development of Government revenue. If government revenue is large from the tourism market, the allocation for regional income will be high because it affects the number of outside communities entering the area. The government also has the responsibility to promote and increase the tourism market because if it is not promoted and allocated properly it will be lost by the times and the characteristics of an area will disappear by itself. This study aims to look at the influence of the tourism market on regional income in Tuk-Tuk. The method used is by distributing questionnaires to entrepreneur owners who offer traditional products. Researchers have a target is a traditional product derived from tuk-tuks. The population and samples were taken from traders in the tuk-tuk who have traditional handicrafts that show the peculiarity of the islands in Samosir.